Religious Books, the French Revolution and the Printer Jean-Baptiste Collignon in Metz - McLeod, Jane; Girard, Renée (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2015)
When the Revolutionary government in France declared Freedom of the Press in 1789 it did not anticipate the flow of counter-revolutionary pamphlets attacking its decision to nationalize the French Church and require all clergy to swear an oath to the Civil Constitution of the Clergy. This article examines the conditions surrounding the printing of these religious pamphlets by investigating the career of one provincial printer in the border town of Metz—Jean-Baptiste Collignon—who worked with émigré bishops to produce them and who was guillotined in 1794 for counterrevolutionary activities. The authors explore the production and distribution of religious pamphlets, the ideological commitment of revolutionary printers, and the regional nature of censorship in the early French Revolution.